(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
Chemotherapy has several adverse effects on the oral cavity, including xerostomia, dysphagia, and mucositis. The therapeutic approach to the adverse effects of chemotherapy on the oral mucosa is insufficient by health programs. Complementary therapies emerge as an alternative to counteract adverse effects caused during and after chemotherapy on the oral cavity. This paper aims to analyze the possible use of complementary therapies on oral mucositis caused by conventional chemotherapy used in the Chilean state guarantee program (GES).